A first approach to identifying cardiotoxic effects of breast cancer chemotherapeutic treatment in Kazakhstan - Zhenisgul Tlegenova; Saule Balmagambetova; Bekbolat Zholdin; Gulnara Kurmanalina; Iliada Talipova; Arip Koyshybaev; Ainel Urazova; Dinara Nurmanova; Olzhas Urazayev; Gulmira Sultanbekova; Kulparshan Kubenova; Mira Baspayeva (National Scientific Medical Center, 2022)
As known, the clinical efficacy of chemotherapy is limited by the cardiotoxicity of drugs used. The study aimed to clarify cardiotoxic complications of chemotherapy from the Aktobe Medical Center database for 2018-2019.        Material and methods: We performed a register study on essential parameters of the oncological process, drugs used, duration of chemotherapy, types of complications, and outcomes, including survival. Results: We found a total of 305 breast cancer cases. Chemotherapy was completed without complications in 65.9% of patients; treatment was interrupted due to complications - 10.5%; 6.2% of cardiovascular complications were identified. The two groups of patients, EchoCG + and EchoCG -, showed significant difference in the number of detected CV complications (p<.001) but no difference in the survival rate (p .814). The survival rate in patients with documented CV complications was 28.1 months vs. 34.3 months in the group without ones (p.005). The survival rate in those who completed the treatment without complications, was 34.9 months vs. 17.6 in individuals whose treatment was interrupted due to complications (p<.001). We performed a detailed review of four cases of cardiotoxicity with fatal outcomes.   Conclusion: The analysis indicates the absence of a systematic approach to recording crucial information regarding cardiotoxicity. There is a lack of concordance in the actions of cardiologists and oncologists in the management of BC patients. The presence of lethal outcomes of chemotherapy with an established cause of cardiac death indicates the need to revise the cancer register management from the standpoint of cardio-oncology. In general, there is a need to develop local protocols for screening and monitoring patients undergoing cardiotoxic chemotherapy and radiation therapy.